Das Mittelalter : Perspektiven mediävistischer Forschung (Akademie Verlag, 1996)
This journal, published by the Mediävistenverband since 1996, provides a forum for interdisciplinary Medieval Studies. Each issue covers a different topic from many different viewpoints. The journal presents recent results, discussions, and new books for the various disciplines and explorers their importance to medievalists as a whole.